On the design of a miniature haptic ring for cutaneous force feedback using shape memory alloy actuators - Hwang, Donghyun; Lee, Jaemin; Kim, Keehoon (IOP PUBLISHING LTD, 2017)
This paper proposes a miniature haptic ring that can display touch/pressure and shearing force to the user's fingerpad. For practical use and wider application of the device, it is developed with the aim of achieving high wearability and mobility/portability as well as cutaneous force feedback functionality. A main body of the device is designed as a ring-shaped lightweight structure with a simple driving mechanism, and thin shape memory alloy (SMA) wires having high energy density are applied as actuating elements. Also, based on a band-type wireless control unit including a wireless data communication module, the whole device could be realized as a wearable mobile haptic device system. These features enable the device to take diverse advantages on functional performances and to provide users with significant usability. In this work, the proposed miniature haptic ring is systematically designed, and its working performances are experimentally evaluated with a fabricated functional prototype. The experimental results obviously demonstrate that the proposed device exhibits higher force-toweight ratio than conventional finger-wearable haptic devices for cutaneous force feedback. Also, it is investigated that operational performances of the device are strongly influenced by electro-thermomechanical behaviors of the SMA actuator. In addition to the experiments for performance evaluation, we conduct a preliminary user test to assess practical feasibility and usability based on user's qualitative feedback.
Keywords: TACTILE DISPLAY